Student Choice between Computer and Traditional Paper-and-Pencil University Tests: What Predicts Preference and Performance? - Lightstone, Karen; Smith, Steven (Revue internationale des technologies en pédagogie universitaire / International Journal of Technologies in Higher Education, 2009)
AbstractTwo studies were conducted to assess meta-cognitive and individual difference influences on students’ choice of writing tests in paper-and-pencil or computer-administered format. In Study 1, university students chose the test format for an accounting exam (paper-and-pencil or computer). In Study 2, students disclosed their reasons for their choice of test format, predicted their scores on the first test and provided confidence ratings for their predictions. The results of both studies show that the reasons for choosing a computer vs. a paper-and-pencil test format differ, and that both choice and performance can be explained to some extent by individual difference and meta-cognitive factors.